Pemuda Cerdas Digital: Pelatihan Desain Grafis dengan Canva di SMA Imelda Medan - Ika Yusnita Sari; Elvika Rahmi; Khairunnisa Khairunnisa; Maristella J Lumbanbantu; Astrida N Marpaung (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2024)
The program titled "Pemuda Cerdas Digital: Pelatihan Desain Grafis dengan Canva" aims to equip young individuals with essential graphic design skills using Canva, a user-friendly design tool. In the digital age, visual communication plays a crucial role in personal branding, marketing, and effective messaging. However, many youths lack access to affordable and accessible design tools and training. This training program provides a hands-on approach to learning graphic design, focusing on practical skills and creative techniques using Canva. Participants are introduced to various design elements such as layout, typography, and color theory, enabling them to create visually appealing materials including social media graphics, posters, and flyers. The program's objective is to enhance participants' design skills, foster creativity, and empower them to effectively communicate ideas through visual content. The training also aims to bridge the gap between traditional graphic design education and the need for accessible, practical tools for the younger generation. Evaluation of the program indicates a significant improvement in participants' ability to produce professional-quality designs and a greater confidence in their design skills. The program highlights the importance of integrating digital tools into youth education to prepare them for future opportunities in a visually-driven world.